Desenvolvimento de atitudes pró-ambientais em atividades do projeto de educação ambiental em escola da cidade de Santa Maria - Schmitz, Gabriela Luisa (2018)
Due to man's exploratory and depredatory actions using the natural resources aiming at the economic gains of society and the development of new technologies, a situation of imbalance of the environmental equilibrium and the man-environment relationship was developed. Concerned about reversing this situation and seeking an improvement in the quality of life and the relationship with nature, international institutions such as UNESCO proposed the Environmental Education (EE) as a tool to develop in all citizens an environmental awareness and development of pro-environmental attitudes that can be externalized as pro-environmental behaviors, according with the Theory of Reasoned Action. In this way, it will be possible to achieve the sustainable development. An EE project can be an important way to promote an attitudinal change in children and for this, this work evaluated the efficiency of the participation an EE program to increase the pro-environmental attitudes of children of a public school of the city of Santa Maria/RS, through their declarations of intention to behave pro-environmentally and their environmental knowledge. Analysis of variance (ANOVA) was used for statistical evaluation of the increase in pro-environmental attitudes and knowledge and linear regression was used to evaluate the correlation between environmental knowledge and pro-environmental attitudes students. After to participate in the environmental education programs, students demonstrated more positive attitudes towards the environment when compared to their attitudes at the beginning of the program and with non-participant students, as well as an increase in their knowledge about the environment. The environmental knowledge of the students showed no correlation with their pro-environmental attitudes, indicating a deficiency of knowledge influencing the students' environmental attitudes. The results obtained in this study corroborate with those in the literature about EE programs and suggest that these programs are efficient and important tools to increase the participants' attitudes and environmental knowledge.